BESS-Set: A Dataset for Cybersecurity Monitoring in a Battery Energy Storage System - Giovanni Battista Gaggero; Alessandro Armellin; Giulio Ferro; Michela Robba; Paola Girdinio; Mario Marchese (IEEE Open Access Journal of Power and Energy)
Smart grids are nowadays featured by distributed energy resources, both renewables, traditional sources and storage systems. Generally, these components are characterized by different control technologies that interact with the generators through smart inverters. This exposes them to a variety of cyber threats. In this context, there is a need to develop datasets of attacks on these systems to evaluate the risks and allow researchers to develop proper monitoring algorithms. This paper addresses this need by presenting BESS-Set, an open-source dataset for cybersecurity analysis of a Battery Energy Storage System (BESS).